Transisi Bisnis Penipuan Online “Sobis” Menjadi Usaha Produktif Dalam Menciptakan Lapangan Kerja Yang Positif Di Lingkungan Masyarakat Kabupaten Sidenreng Rappang - jumriah basri, Jumriah Basri; Putri D, A. Kartini Sari; Wirdana, Sri; Ayu, Ari; Nurwafiyyah, Auliyah (Amkop Management Accounting Review (AMAR), 2025)
The urgency of this research lies in the pressing need to understand and address the socio-economic impact of "Sobis" in Sidenreng Rappang Regency. The proposed solution is to redirect former perpetrators toward legal businesses in order to reduce cybercrime, improve welfare, create job opportunities, and strengthen the local economy. This study employs a qualitative-descriptive method, using phenomenology and case study techniques. The findings show that the transition of former online fraud perpetrators in Sidenreng Rappang Regency has brought positive impacts on economic, social, and psychological aspects. Economically, although legal income is smaller, their financial condition is now more stable, organized, and allows for savings. Socially, they are better able to adapt, leave behind a false luxurious lifestyle, and build a positive image through legal businesses. Psychologically, they experience greater peace and more stable happiness compared to their past, which was full of stress and paranoia. Awareness of legal consequences also strengthens their determination not to return to illegal activities. In short, this transition results in economic stability, social modesty, and psychological calmness.